Slurs and the Type-Token Distinction of Their Derogatory Force - Liu, Chang (Rivista Italiana di Filosofia del Linguaggio)
Slurs are derogatory, and theories of slurs aim at explaining their “derogatory force”. This paper draws a distinction between the type derogatory force and the token derogatory force of slurs. To explain the type derogatory force is to explain why a slur is a derogatory word. By contrast, to explain the token derogatory force is to explain why an utterance of a slur is derogatory. This distinction will be defended by examples in which the type and the token derogatory force come apart. Because of the distinction, an adequate theory of slurs must be plausible for both the type and the token derogatory force. However, I will argue that many theories fail to be plausible for both. In particular, Hom’s combinatorial externalism and the conventional implicature theory offer implausible accounts of the token derogatory force, whereas the prohibitionist theory is insufficient to explain the type derogatory force.